2004
DOI: 10.1002/nau.20018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of pelvic floor muscle function in continent and incontinent women

Abstract: Visual inspection and digital tests are easy and reliable methods by which insight can be gained into the multi-muscular activity and coordination of the pelvic floor and lower abdominal muscles in continent and incontinent women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
4
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 41 publications
6
100
4
14
Order By: Relevance
“…Visual inspection and digital tests are easy and reliable methods by which insight can be gained into the multi-muscular activity and coordination of the PFM and lower abdominal muscles in continent and incontinent women (14). Lynch and Aronoff (15), in a small sample size, observed better agreement using the tampon scale than the digital scale.…”
Section: Introductionmentioning
confidence: 99%
“…Visual inspection and digital tests are easy and reliable methods by which insight can be gained into the multi-muscular activity and coordination of the PFM and lower abdominal muscles in continent and incontinent women (14). Lynch and Aronoff (15), in a small sample size, observed better agreement using the tampon scale than the digital scale.…”
Section: Introductionmentioning
confidence: 99%
“…To date, PFM passive properties are estimated by introducing a finger, a pressure probe or a dynamometric speculum into the vaginal cavity. For digital examination, Devreese et al (2004) reported the use of a 3-point scale (normo-, hypo-, hypertone) in continent and incontinent women. However, despite its usefulness in a clinical setting, this assessment technique remains subjective.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson et al [5] found a significant correlation between TAUS and transperineal ultrasonography, and manual muscle testing for PFMs contraction. Several studies have assessed PFMs function in women by using TAUS and transperineal ultrasonography [12,22,23].…”
Section: Discussionmentioning
confidence: 99%